Ageing and dysregulated lung immune responses in fatal COVID-19 - de Souza Xavier Costa, Natália; de Brito, Jôse Mara; Froio, Carla; Ribeiro Júnior, Gabriel; Lamounier, Ana Carolina Alves; Antonangelo, Leila; Faria, Caroline Silvério; Ito, Juliana Tiyaki; Santos Lopes, Fernanda Degobbi Tenorio Quirino do; de Almeida Monteiro, Renata Aparecida; Duarte-Neto, Amaro Nunes; Saldiva, Paulo Hilário Nascimento; et al. (Immunity & ageing, 2025)
Elderly individuals were disproportionally affected during the COVID-19 pandemic, and more than 80% of the global COVID-19-related deaths between 2020 and 2021 occurred among people aged 60 years or older. Several cellular modifications in aged cells may lead to systemic inflammation and fibrotic responses. Age or exogenous insults induce cellular senescence, further increasing the release of pro-inflammatory mediators, leading to the condition known as inflammaging, that can contribute to disease severity. Older individuals presented signs of systemic hyperinflammation in severe COVID-19, but few studies analyzed the influence of age on lung tissue responses in cases of severe COVID-19. We hypothesized that age related alterations regarding innate/acquired immunity and cellular senescence in lung tissue of individuals without lung diseases could predispose to viral infection. We also aimed to identify how the aged lung responded to severe COVID-19 infection. We studied lung tissues from 19 individuals that died from non-pulmonary causes and 28 adult individuals who died from COVID-19 between March and May of 2020, divided according to their age (> or < 60 years). Tissue sections were stained, via immunohistochemistry, and 19 markers among immune cells, COVID-19 receptors, cytokines and senescence were analyzed in the lung parenchyma of both groups. In the COVID-19 group, the Luminex multiplex assay technique was used to detect a panel of 25 cytokines/chemokines. In control lungs, aged individuals had a lower TLR7 expression, without differences in other markers. Older patients had a shorter time between onset of symptoms and death, with a significant negative correlation with age. Unlike the adult younger group, older COVID - 19 patients presented significant differences in relation to their age matched controls in the expression of CD8 + T cells, IFN-α2, TLR7, pSTAT-3, p21 and p53. They also presented higher protein expression that IFN-α2 and TGF-beta than the adult COVID-19 group, with a trend to decreased CD20 + cell density in the lungs. Taken together, our data show age adversely affects the lung expression of key proteins related to COVID-19 susceptibility and severity, by perpetuating inflammation and increasing pro-fibrotic responses.